IMF Survey, Volume 36 Issue 07. - International Monetary Fund. External Relations Dept. (Washington, D.C. : International Monetary Fund, 2007)
Spring Meetings focus on global growth, imbalances; IMFC communique; economic outlooks for Western Hemisphere, sub-Saharan Africa, Asia, and Europe; Aid for Lebanon's recovery; United Kingdom reaps fruits of reform; China's growth examined.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet